Implication of Agricultural Science Education on the Development of the Nigerian Economy - Innocent-Ene, , E. O.,; Suleiman, , A. D.; Sanni, , J. (Kashere Journal of Education, 2021)
The introduction of agricultural education in Nigeria educational system is necessary as it helps learners acquire knowledge and skills in agriculture which will improve the quantity and quality of agricultural production with a view to better the living standard of the people. Agricultural education has been progressing overtime due to the benefits derived from agriculture. The agricultural sector is a major source of livelihood for most citizens, but the paper noted that production hurdles have significantly stifled the performance of the sector. The paper argued that if the problems bedeviling agricultural sector as well as agricultural education such as inadequate funding, low societal acceptance, lack of qualified manpower, lack of good roads and infrastructures among others can be addressed, the Nigerian economy will be in a better shape as it relates to food security, employment of the youth and provision of raw materials. The paper finally concluded that agricultural education is an innovative programme aimed at self-reliant and employment creation in the country. Apart from the income generation and economic empowerment it can give to the youths, it preoccupies them and keep their minds out of mischief and violence, thereby, enhancing peace and national security which are of utmost importance to the Nigerian economy, and recommends adequate funding to acquire necessary tools and equipment, qualified teaching personnel and in-service training for the teachers as well as incentives for learners of agricultural science.